Resveratrol facilitates bone formation in high-glucose conditions - Hwang, Sung-Min; Kim, Tae-Young; Kim, Anna; Kim, Yong-Gun; Park, Jin-Woo; Lee, Jae-Mok; Kim, Jae-Young; Suh, Jo-Young (Frontiers in Physiology, 2024)
Periodontitis is known to be affected by high-glucose conditions, which poses a challenge to periodontal tissue regeneration, particularly in bone formation. In this study, the potential effects of resveratrol (3,5,4’-trihydroxystilbene, RSV) in facilitating bone formation under high-glucose conditions after periodontitis has been investigated. We focused on the analysis of osteoblasts and periodontal ligament cells, which are essential for bone formation including cell proliferation and differentiation. And we aimed to investigate the impact of RSV on bone healing, employed diabetic mouse model induced by streptozotocin and confirmed through histological observation. High-glucose conditions adversely affected cell proliferation and ALP activity in both MC3T3-E1 and hPDLF in vitro, with more significant impact on MC3T3-E1 cells. RSV under high-glucose conditions had positive effects on both, showing early-stage effects for MC3T3-E1 cells and later-stage effects for hPDLF cells. RSV seemed to have a more pronounced rescuing role in MC3T3-E1 cells. Increased ALP activity was observed and the expression levels of significant genes, such as Col 1, TGF-β1, ALP, and OC, in osteogenic differentiation were exhibited stage-specific expression patterns. Upregulated Col 1 and TGF-β1 were detected in the early stage, and then ALP and OC expressions became more pronounced in the later stages. Similarly, stronger positive reactions against RUNX2 were detected in the RSV-treated group compared to the control. Furthermore, in in vivo experiment, RSV stimulates the growth and differentiation of osteoblasts, thereby promoting bone formation. High-glucose levels have the potential to impair cellular functions and the regenerative capacity to facilitate bone formation with MC3T3-E1 rather than hPDLF cells. Resveratrol appears to facilitate the inherent abilities of MC3T3-E1 cells compared with hPDLF cells, indicating its potential capacity to restore functionality during periodontal regeneration.